Effect of grassland degradation on soil quality and soil biotic community in a semi-arid temperate steppe - Han, Xu; Li, Yuhui; Du, Xiaofang; Li, Yingbin; Wang, Zhengwen; Jiang, Siwei; Li, Qi (Ecological processes, 2020)
Grasslands provide a number of ecosystem services for human society. Degradation of grasslands results in the loss of biodiversity and leads to the deterioration of ecosystem functions. In order to accurately assess the influence of grassland degradation on belowground ecosystems, we conducted experiments on a temperate steppe with different levels of degradation and investigated the influence of degradation on soil quality and soil biotic communities. Our results showed that grassland degradation significantly decreased soil quality, with lower values of soil quality index (SQI) observed in the degraded grassland than the meadow steppe and the grassland from the forest-steppe ecotone. Changes in the SQI along the grassland degradation gradient were positively correlated with soil carbon stock and the aboveground biomass, and negatively correlated with the root shoot ratio. Nematode trophic diversity and the ratio of fungal to bacterial PLFA were lower in the degraded grassland than the grassland from the forest-steppe ecotone. The dissimilarities in soil microbial and nematode community composition increased with the changes in soil quality index. Our results indicate that soil quality index based on the minimum data sets could effectively assess the influence of grassland degradation on soil biodiversity and ecosystem function. In order to effectively restore degraded grasslands, the key contributors to the soil quality, such as soil carbon, should be taken on priority basis for revitalizing the soil biodiversity and ecosystem function.